Analisis Faktor-Faktor yang Mempengaruhi Minat Berwirausaha Mahasiswa (Studi Kasus pada STMIK Mikroskil Medan) - Eko Yuliawan; Mbayak Ginting (Lembaga Penelitian & Pengabdian pada Masyarakat (LPPM) Universitas Mikroskil, 2012)
In Indonesia the graduated university students need a relative long time to get a job, so there are many unemployed workers from various universities. Entrepreneurship is a key to overcome the unemployement from graduated student. For that reason the student’s interest on running a private enterprise is needed to develop in campus. The result of this research has found that personal variable, social environment, demography and availablity of information, ownership of social network and the syncronous capital access has influenced the student’s interest on running a private enterprise. Whereas the partial experiment had shown that personal variable, the availability of entrepreneurship information and the ownership of social network have influenced the entrepreneurship interest, whereas the environment variable, demography and the capital access are not influence towards the student interest on running a private enterprise. Based on this research, has been found the coefficient of determination as many as 0,321, it means that personal variable, social environment, demography, availability of entrepreneurship information, the ownership of social network and financial capital access, can explain the student’s interest on running a private enterprise as many as 32,1%. Personal variable and environment are partialy influence toward the student’s interest on running a private enterprise, whereas demography variable is not partially influence towards the interest on running a private enterprise by the students of STMIK Mikroskil Medan.